The Auditor Change, Audit Opinion, and Corporate Governance to Reduce Audit Delay: Does Public Accounting Firm Reputation Matter? - Taufiq, Abd. Rohman; Murwani, Juli; Srijani, Ninik; Chapuze, Amaury Capdeville; Widura, Wiko (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Objectives: The study aims to find out the effect of auditor turnover, opinion, and corporate governance on audit delay with accounting firm's reputation as a moderation. Method: this type of research is quantitative research. the population in the study was a consumer goods company registered with the idx for the period 2017-2021. Sampling technique using purposive sampling method and obtained data as many as 135 samples. Data analysis techniques use multiple linear regression and moderate regression analysis. Results: The results showed that the change of auditor had no effect on audit delay, while audit opinion and audit committee had a negative and significant effect on audit delay, while the independent board of commissioners had a positive and significant effect on audit delay. The results of this study also showed that accounting firm's reputation was able to positively moderate audit opinions against audit delays, but accounting firm's reputation was unable to moderate the audit committee against audit delays